Ants Doing Legwork: Investigating Motivators for Software Development Career Abandonment - Oliveira, Ruan; Massoni, Tiago; Araújo, Narallynne; Sarmento, Camila; Santos, Francielle (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2021)
Context: Career abandonment (turnaway) among software developers may be associated with many factors related to the profession. Identifying and understanding how these factors can affect those professionals is essential for organizations to design more effective retention policies and better understand the phenomenon. Objective: This study aims to identify motivators that may be associated with the turnaway phenomenon among software developers, in addition to dimensions with which those motivators are associated. Method: A qualitative study was conducted with 15 former software developers from different regions of Brazil. Results: We have identified 49 different motivators, among which the most cited were professional stagnation, lack of financial recognition, lack of professional regulation, and work overload, among others. We classified those motivators into seven software engineering dimensions, mainly: software engineering professional practice, management, and economics. Conclusion: The results of the study suggest, grounded on the collected qualitative data, a number of hypotheses to further research, relating turnaway to the types of activities of software development. We hope these results contribute to devise effective strategies for organizations to retain developers, additionally minimizing the social cost of turnaway to those developers.